Perkembangan Dakwah Islam pada Masyarakat Tradisional - Moh Amin; Bambang Sugiyanto (Resolusi: Jurnal Sosial Politik, 2021)
This study intends to examine the phenomenon of Islamic da'wah in the village of Kedungwringin, Kebumen, which is a village with a traditional community. By using observation and interview methods to obtain primary and secondary data, this study concludes several points. Among other things, namely, that in a society that is thicker with the practice of Kejawen and the location of the village which is not very strategic, da'wah activists will face challenges that are quite difficult to overcome. Coupled with the needs of the community, preachers need to consider creative da'wah methods so that they can be accepted by the community more openly.